The typical presentation of an atypical pathogen during an outbreak of Legionnaires’ disease in Vila Franca de Xira, Portugal, 2014 - Dias, A. (2018)
Background: An outbreak of Legionella pneumophila serogroup 1, with 403 cases was identified on the 7th November 2014 in Vila Franca de Xira, Portugal. Outbreak source was the wet cooling system of a local factory. Hospital Pulido Valente was one of the hospitals receiving patients with Legionnaires’ disease (LD). Methods: We describe the clinical findings and diagnostic methods used among the 43 confirmed or probable cases admitted to our department. Results: 60.5% were male, mean age was 56.1 ± 13.5 years and tobacco smoking was the most frequent risk factor (76.7%). All patients had fever, 62.8% ≥39.5 ◦C, 72.1% had chills and myalgia/arthralgia and 62.8% had dry cough. Extra pulmonary symptoms were frequent: confusion and headache occurred in 34.9% and gastrointestinal symptoms in 20.9%. High C-Reactive Protein (55.8% ≥30 mg/dL) and hyponatremia (62.8%) were the laboratorial abnormalities most commonly found. Hypoxemia occurred in 55.8% and hypocapnia in 93%. Urinary Antigen Test (UAT) was positive in 83.7% of the cases. Conclusions: Although not specific, a combination of risk factors, symptoms and laboratory findings can be highly suggestive of LD, even in an outbreak. This should prompt diagnosis